2005
DOI: 10.6090/jarq.39.135
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of High Temperature Inhibition in Tomato Fruit Set by Plant Growth Regulators

Abstract: The effects of plant growth regulators on fruit set of tomato (Lycopersicon esculentum Mill.) under high temperature were examined in a controlled environment and a field under rain shelter. Tomato plants exposed to high temperature (34/20ºC) had reduced fruit set. Treatments of plant growth regulators reduced the fruit set inhibition by high temperature to some extent, especially treatment with mixtures of 4-chlorophenoxyacetic acid (4-CPA) and gibberellins (GAs). In the field experiment, tomatoes treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 11 publications
4
29
0
4
Order By: Relevance
“…This might be occurs due to application of auxin at the time of flowering and resulted lower flowers drop. This result is in agreement with the findings of Baliyan et al (2013) and Sasaki et al (2005) where they reported that, tomato treated with 4-CPA showed higher in flower and fruit set. Sarkar et al (2014b) and Choudhury et al (2013) also reported that, plant growth regulators has great potential to facilitate the flower and fruit setting as well as yield of summer tomato.…”
Section: Resultssupporting
confidence: 83%
“…This might be occurs due to application of auxin at the time of flowering and resulted lower flowers drop. This result is in agreement with the findings of Baliyan et al (2013) and Sasaki et al (2005) where they reported that, tomato treated with 4-CPA showed higher in flower and fruit set. Sarkar et al (2014b) and Choudhury et al (2013) also reported that, plant growth regulators has great potential to facilitate the flower and fruit setting as well as yield of summer tomato.…”
Section: Resultssupporting
confidence: 83%
“…Earlier research also indicates increased fruit setting and fruit size in tomato due to application of plant growth regulators such as 2,4-D and 4-CPA at low concentrations (Khan et al, 2006).The most widely available plant growth regulator is GA 3 and its application in tomato plants has been shown to induce marked stem elongation, increase fresh weight, accelerate flowering and produce greater numbers of flowers per plant and increase fruit set, (Davies, 1995;Kazemi et al, 2014). It is well documented in the literature that a mixture of 4-CPA and GA 3 have shown an increased tomato fruit set and proportion of normal fruits compared to plants of the same crop treated with 4-CPA (Sasaki et al, 2005). Thus, hormonal use in the plant system and their importance is the outstanding discovery and achievement of plant sciences.…”
Section: Issn: 2319-7706 Volume 7 Number 08 (2018)mentioning
confidence: 96%
“…(Sasaki et al, 2005). Earlier research also indicates increased fruit setting and fruit size in tomato due to application of plant growth regulators such as 2,4-D and 4-CPA at low concentrations (Khan et al, 2006).The most widely available plant growth regulator is GA 3 and its application in tomato plants has been shown to induce marked stem elongation, increase fresh weight, accelerate flowering and produce greater numbers of flowers per plant and increase fruit set, (Davies, 1995;Kazemi et al, 2014).…”
Section: Issn: 2319-7706 Volume 7 Number 08 (2018)mentioning
confidence: 99%
“…GA 3 telah diketahui mampu meningkatkan fruit set dan hasil buah tomat pada konsentrasi yang rendah (Sasaki et al, 2005;Khan et al, 2006). Namun, buah tomat hasil induksi giberelin memiliki ukuran lebih kecil dari pada buah berbiji yang menunjukkan bahwa adanya peranan hormone lain terhadap pertumbuhan dan perkembangan buah tomat (de Jong et al, 2009).…”
Section: Pendahuluanunclassified